Brief Overview of Immunosuppressive Regimens in Animal Models for Vascularized Composite Allotransplantation - Aline Yen Ling Wang (Highlights on Medicine and Medical Research Vol. 8, 2021)
The development of vascularized composite allotransplantation (VCA) and its clinical need has led to the need for more animal models to study and perform the research required to further this specialty in terms of functional recovery and immunomodulatory improvements. Most of the research currently being done in the VCA is to improve the safety profile of such procedures, in particular with the need to improve immunosuppressive regimens. Much of the animal models are reported in individual series in the literature but there has not been a review as such of these models. Here we present a compilation of the animal models reported in the literature thus far in VCA. A comprehensive review of the literature was performed for any studies which involved the use of animal models in various aspects of VCA research. The models were organized according to the type of VCA transplant, whether they were orthotopic or heterotopic, immunosuppressive regimen each study used and investigation purpose. Twenty-two facial transplant models were reported, 3 abdominal wall transplants, 4 penile transplantations, 21 uterus transplantations, 13 hindlimb transplantations and 4 myocutaneous flap transplantation animal models were reported. Primates, swine, rats, mice, rabbits, sheep and dog animal models in VCA were also reported. The most used immunosuppressive drugs are calcineurin inhibitor such as cyclosporin A and tacrolimus in these VCA animal models. They can significantly suppress lymphocyte function by blocking the phosphatase activity of calcineurin of lymphocytes. They are sometimes used combined with mycophenolate mofetil or steroids or antilymphocyte serum. The review of existing animal models will allow further research to be focused in other areas of VCA where there is a current paucity of literature. The immunosuppressive regimens used in each animal model can also be reviewed to determine which regimen works in which type of animal model which will save time and resources for future research.